Nama : Awaliyatul Adawiyah Judul : Analisis Uji Organoleptik dalam Pembuatan Yoghurt dari Tiga Jenis Susu Kurma yang Berbeda - Adawiyah, Awaliyatul; Apriningrum, Nelly; Elvandari, Milliyantri (Innovative: Journal Of Social Science Research, 2024)
The Faculty of Industrial Engineering (FRI) Telkom University National Campus (TUNC) faces challenges in monitoring the performance of lecturers based on the Tri Dharma of Higher Education which includes teaching, research, and community service. The main challenge is the absence of an integrated system that can monitor all Tri Dharma activities at the Faculty of Industrial Engineering, especially with the merger of the four Telkom University campuses. This study aims to design a management information system that can integrate lecturer performance data at the Faculty of Industrial Engineering TUNC. The method used is Rapid Application Development (RAD), which enables rapid system development through iterations and prototypes. This approach ensures that the system developed is in accordance with user needs and can receive continuous input. The result of the research is a lecturer performance monitoring management information system that is able to collect, process, and manage data centrally. The implementation of this system is expected to provide significant benefits for the Faculty of Industrial Engineering, namely improving the quality of lecturer data management, facilitating the process of monitoring and evaluating lecturer performance, and supporting data-based decision making. This system is also expected to be a model for other faculties at Telkom University and other universities in managing lecturer performance data.